2020
DOI: 10.1186/s13643-020-1287-y
|View full text |Cite
|
Sign up to set email alerts
|

Situation analysis of onchocerciasis in Cameroon: a protocol for systematic review of epidemiological studies and impact of disease control interventions

Abstract: Background: Many control methods have been implemented to tackle onchocerciasis and great successes have been achieved, leading to a paradigm shift from control of morbidity to interruption of transmission and ultimately elimination. The mandate of the African Programme for Onchocerciasis Control (APOC) ended in 2015, and endemic countries are to plan and conduct elimination activities by themselves, with technical assistance by the Expanded Special Project for Elimination of Neglected Tropical Diseases (ESPEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…50 The finding of this systematic review and meta-analysis is much higher than other findings reported from different parts of the world. It is higher than review reports from Switzerland, 51 France, 52,53 Canada, 54 Spain, 55 Nigeria, 56 Cameroon. 57 However, the pooled prevalence of onchocerciasis was lower than the study from Brazilian Amazon, 58 and Burkina Faso.…”
Section: Meta-regressionmentioning
confidence: 69%
“…50 The finding of this systematic review and meta-analysis is much higher than other findings reported from different parts of the world. It is higher than review reports from Switzerland, 51 France, 52,53 Canada, 54 Spain, 55 Nigeria, 56 Cameroon. 57 However, the pooled prevalence of onchocerciasis was lower than the study from Brazilian Amazon, 58 and Burkina Faso.…”
Section: Meta-regressionmentioning
confidence: 69%
“…East Africa Science 2024 | Volume 6 | Number 1 Drug Administration (MDA), vector control and recent intervention trials, the onchocerciasis still present in some areas with high prevalence. 9,10 Therefore, the World Health Organization (WHO), International foundations, Governmental and Non-Governmental Organisations worked together to reduce the burden of onchocerciasis in endemic zones. 11,12 They used insecticide sprays as well as bi-annual mass administration of ivermectin and a positive impact has been achieved.…”
Section: Despite Control and Elimination Efforts Through Massmentioning
confidence: 99%
“…In highly endemic foci, ivermectin treatment alone might not be enough to eradicate the parasite (Lakwo et al, 2020). Also, in foci of co‐endemicity with Loa loa , ivermectin cannot be used for community‐based mass‐treatments, due to severe side‐effects (Nana Djeunga et al, 2020; Boussinesq et al, 2018). Considerable research has been conducted on bacterial insecticides over the last decades, and major successes have been obtained (Guillet et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Still alternative and complementary strategies to drug treatment are needed. Such measures could be the destruction of Simulium breeding sites by clearing the vegetation support for larvae “slash & clear” strategy (Lakwo et al, 2020) or the strategic use of safe and uncostly larvicides (Nana Djeunga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%